In The Face of Disinflation, Policymakers Are Hesitant to Reduce Interest Rates: is This in Line With Economic Theory? - Li, Shuquan (Transactions on Economics, Business and Management Research, 2024)
This paper approaches the issue by first considering whether such reluctance to lower interest rates even in the face of disinflation is supported by standard economic theory. Expanding through Neo-Fisherianism and reflective equilibrium, this paper examines how counterproductive effects further interest rate cuts could be and whether scope exists for conventional monetary policies. Practical limitations are in line with Keynesian economics prescription on lower interest rates to boost demand. The zero lower bound and liquidity traps render such measures, while not limited to, an inadequate remedy for the ailment as revealed by the not-so-distant experiences during the 2008 credit crunch and current COVID-19 outbreak. The debate also embraces other influences from the globe concerning economics and politics, like exchange rate volatility and public faith in the role of central banks. Since further rate cuts magnify the risks and reduce potential returns, a more appropriate strategy would therefore be a mixed policy approach—to alternative instruments—entailing fiscal stimulus plus quantitative easing in view of disinflation. The paper concludes, therefore, that the cautious approach by policymakers is based on theory as well as on evidence; this therefore underlines the call that responses in policy need to be nuanced and specific to the context.